1304 LAXATIVES PRESCRIPTION MONITORING FOR AN OVERLOOKED PROBLEM. (16th January 2023) - Wong, E; Payab, Q; Justin, J; Nadir, R; Aung, N; O'Malley, F; Gamble, E
Abstract: Introduction: Constipation is a common diagnosis among hospitalized patients. It results in considerable morbidity in elderly patients, healthcare utilization and economic burden. Laxatives are commonly prescribed but poorly monitored due to benign side effect perception. Aim: We undertook a review of the quality of laxative prescribing and subsequent monitoring amongst an inpatient cohort. We propose new standards: - Medication review at least once weekly; - Documented rationale for choice of medication - Specified timeframe review and outcome documentation We reviewed current hospital trust policy of laxative prescribing and produced a new constipation management guideline in response to early audit data. Method: Data collected across medical wards in Trafford General Hospital, Manchester. Data was collected on types of laxatives, reason for prescription, date of review, length of course, compliance and effect of laxatives. Two rounds of audit were performed 6 months apart, with an interim intervention of staff education and local introduction of a new constipation management guideline. The guideline consisted of decision algorithm and suggested treatment. Results: 47 individual prescriptions were audited in round 1 and 72 prescriptions in round 2, this represented 23 and 32 patients respectively. Review of medications within first week of prescription improved from 17% to 83.7% across the two cycles. Documentation of constipation diagnosis improved from 52.2% to 97.2%. There were large percentage improvements in documentation of specified treatment outcomes across all audited fields, despite overall poorer medication compliance among patients in round 2 (56.9% versus 66% in round 1). The average length of laxative use decreased from 18.6 days to 15.3 with overall percentage of patient with constipation resolved increased from 65% in round 1 to 73% in Round 2 Conclusion: Staff education and implementation of treatment guidelines made a substantial improvement to the medical management of constipation in hospitalized patients.